Purchase order for pre shipment inspection (PSI) for access control system for BRAC University new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Bureau Veritas (Bangladesh) Private Limited for PSI for access controlling for Brac University new campus project.